Mechanical vibrations - Rao, Singiresu S., 1944- (Pearson, 2017)
Retaining the style of previous editions, this Sixth Edition of Mechanical Vibrations effectively presents theory, computational aspects, and applications of vibration, introducing undergraduate engineering students to the subject of vibration engineering in as simple a manner as possible. Emphasizing computer techniques of analysis, Mechanical Vibrations thoroughly explains the fundamentals of vibration analysis, building on the understanding achieved by students in previous undergraduate mechanics courses.